DETERMINATION OF THE EPICENTRAL DISTANCE OF AN IMPENDING EARTHQUAKE FROM THE RISE TIME OF SEISMIC ELECTRIC SIGNALS - Varotsos P.; Sarlis N.; Skordas E.; Lazaridou M. (My University, 2003)
An earthquake with magnitude 4.7 occurred on June 13,2003 with an epicenter almost 65 km North of Athens. This was preceded by Seismic Electric Signals recorded at a station lying approximately 30 km ESE of Athens. Beyond other parameters of the impending earthquake, its epicentral distance has been determined well in advance. This paper explains the procedure on which the latter determination was based. The essence of this procedure lies in the fact that the transmission of low frequency electric signals in a weakly conductive medium like the earth, follows diffusion type equations.
Keywords: 528.873